13th World Congress of Food Science &Amp; Technology 2006
DOI: 10.1051/iufost:20060023
|View full text |Cite
|
Sign up to set email alerts
|

Use of X-ray Micro-CT to characterize structure phenomena during frying

Abstract: It is the microstructure that gives the desired textural characteristics to food products. Thus it is of our interest to understand structuring mechanisms in order to be able to design food products with specific textural properties. Furthermore, in the case of frying, consumers demand for healthier foods has initiated interest in understudying the underlying physical phenomena of oil absorption during frying. A number of techniques have been used to quantify internal structures of fried foods (e.g. optical mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Oil was shown to be mainly localized in the surface but was also present in deeper cell layers with the persistence of oil in samples after hexane washing. Miri, Bakalis, Bhima, and Fryer (2006) used an other non invasive technique, X-ray tomography, and made volumetric reconstructions of the microstructure of a fried potato of 1 cm of diameter and 2 cm of length. They showed that pore interconnectivity was limited in the surface of the product, considering the axial and lateral resolution of the X-ray measurement technique of about 6 lm (van Dalen, Nootenboom, van Vliet, Voortman, & Esveld, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Oil was shown to be mainly localized in the surface but was also present in deeper cell layers with the persistence of oil in samples after hexane washing. Miri, Bakalis, Bhima, and Fryer (2006) used an other non invasive technique, X-ray tomography, and made volumetric reconstructions of the microstructure of a fried potato of 1 cm of diameter and 2 cm of length. They showed that pore interconnectivity was limited in the surface of the product, considering the axial and lateral resolution of the X-ray measurement technique of about 6 lm (van Dalen, Nootenboom, van Vliet, Voortman, & Esveld, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…porosity assessment) of the non-hydrated material before and after certain durations of hydration. µCT has proven to be a very useful technique for the non-invasive visualisation and measurement of the internal microstructure of cellular food products, such as porous rice kernels and whipped cream (van Dalen et al, 2003), aerated chocolate and muffins (Lim et al, 2004), bread (Falcone et al, 2004;Lassoued et al, 2007), cornflakes (Chaunier et al, 2007), dough (Mousavi et al, 2005), extruded starches (Babin et al, 2007), French fries (Miri et al, 2006) and biopolymer foams (Trater et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to Fig. 2, as the pore diameter increased, the drying rate increased and evaporation of water was more intense, so more pores, cracks, voids and open channels formed, which contribute to the space available for oil absorption 29 .…”
Section: Effects Of Initial Pore Diameter On the Oil Absorptionmentioning
confidence: 99%
“…Huizenga and Smith 17 observed that the effective vapor diffusivity in porous solids increased with the rise of pore size, which was responsible for the above phenomenon. At the beginning of frying 2 min , moisture evaporates at a very fast rate for all sample with different pore diameters samples, which created an overpressure inside the pores 29 . So the STO contents were all low at 2 min, which was less than 10 .…”
Section: Effects Of Initial Pore Diameter On the Oil Absorptionmentioning
confidence: 99%